Attenuation of early morning surge in blood pressure with special reference to bedroom temperature. - Wang H; Sekine M; Xu F; Kanayama H; Tatsuse T; Uebaba K; Kagamimori S (Journal of the Japanese Society of Balneology, Climatology & Physical Medicine, 2006)
Objective :A rapid rise in blood pressure (BP) in the early morning is called morning BP surge and is known to be related to the onset of cerebrovascular or cardiovascular diseases. Exposure to cold temperature aggravates this condition. However, few studies have investigated the relationship between morning BP surge and bedroom temperature (BT). This study examined the effectiveness of a comfortable BT for mitigating morning BP surge.Methods :In this study, five healthy male university students (22.8+/-0.4 years old with BMI 21.7+/-1.3Kg/m[2]) volunteered to be subjects. The relative humidity in the bedroom was controlled to 50%, and the BT was set at 10 degreesC and 25 degreesC for two test conditions. From 0:00 to 8:00 am, a Portapres Model-2 was used to measure BP continually at each beat. The average BP and heart rate (HR) from 2:00 and 4:00 am were used as the baseline BP and HR. The changing rates of BP and HR from 4:00 to 7:30, the time and the BP value when BP started to rise, the time and the BP value when the BP reached the maxi-mum, the BP value at the time of waking, and the time and rate of increase of BP until it reached the peak at temperatures of 10 degreesC and 25 degreesC were compared by means of the Wilcoxon signed ranking test. Results :The BP before waking started to rise later at 25 degreesC than that at 10 degreesC. BP rose more slowly at the higher BT than at the lower BT, especially 30 minutes after waking. At the lower BT, BP rose almost linearly, and the maximum rising rates were 37% (153.3mmHg) for systolic BP and 54% (97.6mmHg) for diastolic BP. At the higher BT of 25 degreesC, however, BP reached the first peaks about 20 minutes after waking/getting up, and then remained stable. The maximum rising rate was 30% (14.2mmHg) for systolic BP and 33% (86.5mmHg) for diastolic BP. At the higher BT, BP reached the maximum value 40 minutes later for systolic BP and 60 minutes later for diastolic BP. At the lower BT, systolic BP exceeded the normal range, reached 140mmHg 35 minutes after getting up, remained stable for 55 minutes, and then rose to the maximum value of 153.3mmHg. In contrast, at the higher BT, the first peak of BP was significantly lower than that at the lower BT. Furthermore, the differences in BP between the first peak of BP and the BP value at the time of staring to rise and between the first peaks and the BP value at the time of waking up were significantly lower at the higher BT than those at the lower BT. The rising rates of BP from the time when BP started to rise and from the time of waking until reaching the maximum value were significantly lower at the higher BT than those at the lower BT.Conclusions :These results suggest that the margin of the rise in BP, the rising rate of BP, and the peak value of BP in the early morning are significantly lower at a BT of 25 degreesC than those at a BT of 10 degreesC. They also suggest that sleeping at a comfortable BT, especially during winter, may suppress morning hypertension or morning BP surge and indirectly prevent the onset of cerebrovascular and cardiovascular disease as well as related deaths. Although the subjects in this study were healthy young men, it was considered that the benefit of sleeping in warm bedroom for preventing morning BP surge may be increased for the elderly who are highly likely to have already suffered from such underlying diseases as hypertension.